Development of Effective Lightweight Material for Construction Building. - Amphon Jarasjarungkiat; Setsawat Chuaisrinual (My University, 2019)
Abstract Due to an increasing trend of building construction in Thailand. Lightweight concrete has been recently introduced into the structural engineering applications. This study was aimed to investigate two aspects; the first one is studying the properties of Cellular Lightweight Concrete (CLC) and verifying that the lightweight concrete satisfies Thai Industrial Standard (TIS Standard) [12]. To verify with the TIS Standard, investigated properties of CLC are dry unit weight, water absorption and compressive strength. Researcher prepared admixtures with sand cement ratio (S/C), water cement ratio (W/C) and percentage of foam to collect statistical data and analyse. Verified by the standard, specimens that pass the standard criteria will be chosen for proper applications in manufacturing of prefabricated construction materials.
Keywords: Building Construction; Watercement ratio; Building material; Innovations in Concrete and Construction Materials